All Days 2013
DOI: 10.2118/167058-ms
|View full text |Cite
|
Sign up to set email alerts
|

Determining Physical Properties of Unconventional Reservoir Rocks: from Laboratory Methods to Pore-Scale Modeling

Abstract: With the rapid progress of imaging methods it is now possible to obtain detailed rock structure information on different scales, ranging from nanometers to micrometers. Such knowledge facilitates use of pore-scale modeling approaches to predict numerous physical properties based on three dimensional structural data. Pore-scale modeling approaches can simulate different processes in the rock under natural conditions (pressure, temperature, etc.), which are more difficult to simulate in the laboratory. This is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Confined fluid flow in the whole pore system. The combination of DFT and the pore-network modeling approach allows one to effectively upscale physical properties from a single pore to pore system and provides a tool for direct apparent permeability modeling in heterogeneous pore materials with nanoscale porosity.…”
Section: Actual Problems and Challenges Of Molecular Modelingmentioning
confidence: 99%
“…Confined fluid flow in the whole pore system. The combination of DFT and the pore-network modeling approach allows one to effectively upscale physical properties from a single pore to pore system and provides a tool for direct apparent permeability modeling in heterogeneous pore materials with nanoscale porosity.…”
Section: Actual Problems and Challenges Of Molecular Modelingmentioning
confidence: 99%
“…A segmentation or labeling process in the image analysis of rock is a critical step to separate the different phases and areas presented in raw micro-CT images [1,19,20]. The process also converts the attenuated images into a quantitative characterization of the pore geometry.…”
Section: Ternary Segmentationmentioning
confidence: 99%
“…Several authors have recognized the utility of the autocorrelation function. Debye et al showed the relationship between the autocorrelation and scattering functions, and this approach has been applied to analysis of pore structures in sandstones and organic matter in unconventional reservoirs, cements, gels, and porous filters. Autocorrelation has also been applied to extending the scales over which pore structures can be analyzed using scattering techniques. , Recently, the applicability of two-point probability functions, linear functions, and two-point cluster functions to analyze soil microstructures, introducing directional analysis, has been discussed. …”
Section: Introductionmentioning
confidence: 99%